Induction of narcolepsy-like symptoms by orexin receptor antagonists in mice. Issue 8 (20th February 2021) - Kaushik, Mahesh K; Aritake, Kosuke; Cherasse, Yoan; Imanishi, Aya; Kanbayashi, Takashi; Urade, Yoshihiro; Yanagisawa, Masashi
Abstract: Orexins/hypocretins are hypothalamic neuropeptides that promote and stabilize wakefulness by binding to the orexin receptor type-1 (OX1R) and type-2 (OX2R). Disruption of orexinergic signaling results in the sleep disorder narcolepsy in mice, rats, dogs, and humans. The orexin receptor antagonist suvorexant promotes sleep by blocking both OX1R and OX2R. Whereas suvorexant has been clinically approved for the treatment of insomnia because it is well tolerated in experimental animals as well as in human patients, a logical question remains as to why orexin receptor antagonists do not induce overt narcolepsy-like symptoms. Here we show that acute and chronic suvorexant promotes both rapid eye movement (REM) and non-rapid eye movement (NREM) sleep without inducing cataplexy in mice. Interestingly, chronic suvorexant increases OX2R mRNA and decreases orexin mRNA and peptide levels, which remain low long after termination of suvorexant administration. When mice are chronically treated with suvorexant and then re-challenged with the antagonist after a 1-week washout, however, cataplexy and sleep-onset REM (SOREM) are observed, which are exacerbated by chocolate administration. Heterozygous orexin knockout mice, with lower brain orexin levels, show cataplexy and SOREM after acute suvorexant administration. Furthermore, we find that acute suvorexant can induce cataplexy and SOREM in wild-type mice when co-administered with chocolate under stress-free (temporally anesthetized) conditions. Taken together, these results suggest that suvorexant can inhibit orexin synthesis resulting in susceptibility to narcolepsy-like symptoms in mice under certain conditions.